Perlindungan Anak dan Penegakan Hukum: Kajian tentang Hak Restitusi dalam Kasus Perdagangan Anak - Tantimin, Tantimin; Hutauruk, Rufinus Hotmaulana; Nopriensa, Salsabella Dea (Journal of Law & Policy Review, 2024)
Child trafficking cases are one of the fastest-growing crimes in the world. Lack of education and limited information make them vulnerable to being trapped in human trafficking. In the Indonesian legal framework, human trafficking is regulated in Law Number 21 of 2007 concerning the Eradication of Human Trafficking and Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection which regulates the right to restitution. However, there are still weaknesses in law enforcement, namely for any criminal offense that restitution can be submitted, so law enforcement does not necessarily facilitate victims in applying for the right to restitution. The research method used in this study is a normative juridical research method. This approach involves problem analysis using primary reference materials which include statutory regulations as the main source (primary legal materials), as well as various secondary sources of legal materials, such as legal literature, legal books, scientific publications, and scientific articles. discusses the regulation and implementation of criminal sanctions against child traffickers and their rights to restitution to find appropriate and accurate answers. Based on the research results, law enforcement efforts regarding the crime of child trafficking and the right to restitution can be carried out in three stages, namely: during the crime, during the trial of the perpetrator of human trafficking, and after the verdict.